AWARENESS OF HUMAN DIGNITY IN HIGH SCHOOL GRADUATES OF PUŁAWY (1994-2009-2016) - Janusz Mariański (Rozprawy Społeczne)
The following article analyses human dignity from a sociological point of view. Particular attention will is paid to such issues as human dignity in the context of grand values, dignity stance versus pragmatic stance, sense of dignity in situations of private life and public life. These issues will be discussed in the light of sociological research carried out in Puławy in high school graduates and technical secondary schools in the years 1994-2009-2016. In the whole group of high school graduates in 2016, 82,2% of the respondents declared their affiliation to Catholicism; 5,9% described themselves as deeply believers, 55,9% – as believers, 16,8% – as undecided, but attached to religious traditions, 10,8% – as religiously neutral, 9,4% – as non-believers and 1,2% – provided no answer